O processo de internacionalização de empresas de serviços profissionais: o caso da integration consultoria - Zanni, Pedro Pinto (2013)
The current study seeks to contribute to the development of theories that deal with the particularities of the processes of international expansion of professional services firms. For this, we conducted a case study of Integration, a Brazilian consulting firm that has undergone a process of internationalization that stands out not only within Brazil but also internationally. The activity of management consultancy was chosen for being one of the few to guard simultaneously and so clearly all the features of professional services firms described in the literature. It also represents the largest share of international trade in professional services in different countries. From the review of the theory and an initial mapping of the Integration case, we identified the main opportunities for theory development and then designed the research protocol that guided the field survey. The research script was structured from thirty-six initial propositions, organized according to the eclectic paradigm OLI (Ownership, Location, Internalization) conceptual framework and observing the implications of the main characteristics of professional services firms in their internationalization processes. The fieldwork took place between November 2010 and October 2012 and included visits to different Integration’s international operations, where interviews were conducted with company’s partners, directors, consultants and clients. The survey generated extensive empirical material that has gone through editing and categorization processes until they had the consistency needed to sustain each of the twenty-two propositions of this study. Through these propositions, we believe that this thesis offers important contributions to the development of theoretical and empirical knowledge about the internationalization process of professional service firms and to the strengthening of a research agenda related to the theme.